2010
DOI: 10.1007/s12011-010-8803-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Selenium Sources on Productive Performance, Serum and Milk Se Concentrations, and Antioxidant Status of Sows

Abstract: The experiment was conducted to study the effects of different selenium (Se) sources on productive performance, serum and milk Se concentrations, and antioxidant status of sows. A total of 12 sows (Landrace×Yorkshire) with same pregnancy were randomly divided into two groups; each group was replicated six times. These two groups received the same basal gestation and lactation diets containing 0.042 mg Se/kg, supplemented with 0.3 mg Se/kg sodium selenite or selenomethionine (i.e., seneno-DL: -methylseleno), re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 32 publications
2
22
0
3
Order By: Relevance
“…The effect of Se sources addition on plasma total Se concentration appeared dose dependent when organic forms (SY or SO) were supplied, whereas the inorganic form (SS) to provide beyond 0.1 mg/kg of feed failed to increase plasma Se level. Mahan et al (1999) also reported that 0.05 mg/kg supplemental Se from SS allowed plasma Se increase, but that plasmatic Se concentration elevation was greater when the organic Se source was provided (Hu et al, 2011;Zhan et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of Se sources addition on plasma total Se concentration appeared dose dependent when organic forms (SY or SO) were supplied, whereas the inorganic form (SS) to provide beyond 0.1 mg/kg of feed failed to increase plasma Se level. Mahan et al (1999) also reported that 0.05 mg/kg supplemental Se from SS allowed plasma Se increase, but that plasmatic Se concentration elevation was greater when the organic Se source was provided (Hu et al, 2011;Zhan et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The serum T‐AOC was assayed by the reduction in Fe 3+ ‐tripyridyltriazine to Fe 2+ ‐ tripyridyltriazine and expressed as U/ml according to the method of Hu et al. (). The serum CAT activity was measured by analysing the rate at which it caused the decomposition of H 2 O 2 at 240 nm as reported by Zhang et al.…”
Section: Methodsmentioning
confidence: 99%
“…The serum MDA concentration was measured by reaction with thiobarbituric acid at 95°C and expressed as nmol/ml as previously described by Shen et al (2015). The serum T-AOC was assayed by the reduction in Fe 3+ -tripyridyltriazine to Fe 2+ -tripyridyltriazine and expressed as U/ml according to the method of Hu et al (2011). The serum CAT activity was measured by analysing the rate at which it caused the decomposition of H 2 O 2 at 240 nm as reported by Zhang et al (2014), and was expressed as U/ml for CAT activity.…”
Section: Chemical Analysesmentioning
confidence: 99%
“…The MDA concentration in plasma and milk was measured by reaction with thiobarbituric acid at 95 °C and expressed as nmol/ml as previously described by Grotto et al [21]. The T-AOC in plasma and milk were assayed by the reduction of Fe 3+ -tripyridyltriazine to Fe 2+ -tripyridyltriazine and expressed as U/ml according to the method of Hu et al [22]. The measurement of GSH-Px activity of plasma and milk was based on the oxidation of NADPH and expressed as U/ml in accordance with the method of Hernández et al [23].…”
Section: Analysis Of Oxidant and Antioxidant Contentmentioning
confidence: 99%